Helicobacter Pylori Seropositivity in Patients with Ankylosing Spondylitis: What Does It Imply? - Ulutaş, Firdevs; Çobankara, Veli (The European Research Journal, 2026)
Objective: This study investigates clinical factors associated with Helicobacter pylori (H. pylori) seropositivity in patients with ankylosing spondylitis (AS), a condition in which H. pylori has been underexplored.Methods: AS patients meeting the modified New York criteria, aged 18-65 years, without comorbidities and followed between 2022 and 2023, were included. Serum anti-H. pylori IgG and IgA antibodies were measured using ELISA and categorized as negative, positive, or highly positive based on titer levels.Results: The cohort consisted of 243 patients, 36.8% males and 63.2% females, with a mean age of 46.6 years and a mean disease duration of 7.9 years. Logistic regression analysis revealed that increasing age significantly elevated the risk of both IgG and IgA seropositivity. Elevated erythrocyte sedimentation rate was strongly associated with IgA positivity (Odds Ratio [OR]: 3.08, 95% Confidence Interval [CI]: 2.05-4.11), while hypomagnesemia (mean serum Mg: 1.95±0.09) also increased the likelihood of IgA seropositivity (OR: 2.82, 95% CI: 1.05-2.88). Notably, hip involvement emerged as a robust predictor of IgG seropositivity (OR: 3.48, 95% CI: 1.52-6.04), and a history of uveitis was linked to a 1.61-fold increased risk of IgG positivity.Conclusion: The findings suggest that older AS patients with systemic inflammation or low magnesium levels are more likely to exhibit H. pylori infection. Moreover, hip involvement and uveitis may serve as relevant clinical markers warranting H. pylori screening in this population. These associations highlight potential pathogenetic links between microbial triggers and disease expression in AS.